PROBLEMATIKA PEMBELAJARAN PAI DI SMPN PASAK TALAWANG - Santiani, Santiani; Azizah Nur Kumala (Cahaya Ilmu Bangsa Institute, 2025)
This research is motivated by the many problems faced by schools in producing quality PAI learning. The aim of the research is to describe the problems of learning Islamic religious education and solutions to solving problems in Islamic religious learning in SMPN 47 and 67 Bandung City. This research is qualitative research with a case study method. The results of this study indicate that the problems faced in teaching the field of study of Islamic religious education at SMPN 47 and 67 are that many students cannot read and write the Koran properly, so that students' ability to understand Islamic religious education is lacking, students who are not ready to support in learning Islamic religious education, the ability of PAI teachers in terms of managing learning and identifying the characteristics of students is still low. Solutions to problems carried out at SMPN 47 and 67 Bandung City are motivating students in learning activities, providing special guidance on reading the Koran with the Iqro method during lessons, peer tutoring methods, getting used to reading the Koran before starting learning. Besides that, from the educator factor, teachers intensively carry out continuous professional development in an effort to improve pedagogical abilities, especially in managing learning.